Time-to-complication Patterns After Radical Cystectomy: A Secondary Analysis of a 30-day Morbidity Assessment Using the European Association of Urology Quality Criteria for Standardized Reporting - Klemm, Jakob; Rink, Michael; von Deimling, Markus; Koelker, Mara; Gild, Philipp; Shariat, Shahrokh F; Dahlem, Roland; Fisch, Margit; Vetterlein, Malte W (European urology focus, 2023)
Complications following radical cystectomy (RC) have been extensively investigated but evidence on the timing of their occurrence is scarce. We aimed to decipher timing patterns for 30-d complications after open RC for bladder cancer at our institution between 2009 and 2017. Complication data were extracted according to a predefined, procedure-specific catalog following the European Association of Urology criteria for standardized reporting. Timing was assessed for each complication and patterns were compared across urinary diversion types and Clavien-Dindo grades. Overall, 2485 complications occurred in 503/506 patients (99%) in three timing patterns: very early during the first week (bleeding, cardiac, neurological), early after 1 wk (gastrointestinal), and intermediate after approximately 2 wk (wound, infectious complications). Some 90% of complications occurred within the first 2 wk. Major complications (Clavien-Dindo grade ≥IIIa) occurred in 78 patients (15%) after a median of 10 days (interquartile range 4-15). Among patients with a continent diversion, the median time to infectious complications was longer (9 vs 7 d; p = 0.005) and major complications tended to occur later (median 13.5 vs 10 d; p = 0.4) over a wider time span in comparison to those with an incontinent diversion. Close clinical monitoring in both inpatient and outpatient settings after RC is mandatory to detect and adequately manage complications, particularly for more complex continent diversions. PATIENT SUMMARY: The time at which different complication types occur varies after surgical removal of the bladder. It is important to be aware of these times to improve patient-centered care and anticipate possible problems after surgery.
Keywords: pooperační komplikace; Urinary Bladder; lidé; Cystectomy; cystektomie; močový měchýř; výsledek terapie; morbidita; Morbidity; Humans; Postoperative Complications; Treatment Outcome; Urology; urologie